The challenges faced by marine industry in logistics - DR. GIGI. G S,; R. AISHWARIYA, (The journal of contemporary issues in business and government, 2020)
As far as the Indian subcontinent, shipping plays a vital role within the transport sector of India’s economy. Indian Shipping companies, Indian marine sector is at an advantageous position the large coastline of 7,500 km. With a coastline close to 7517 km and twelve major and 187 minor ports India happens to be a possible destination for shipping and trans shipment . This paper comprises of the introduction, the background and challenges faced by the marine industry in logistics, literature review, theoretical aspects of marine logistics. The data analysis and the research findings are discussed. The outcome of the research analysis are mentioned the last it has the details about how to overcome the challenges, methods to solve the issues and improve the marine logistics are been enlightened.